PENGARUH PELAKSANAAN TEHNIK DEEP BREATING (NAFAS DALAM) TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI DI POSYANDU BALADA SEPAKAT DI WILAYAH KERJA PUSKESMAS TANJUNG PAKU KOTA SOLOK - Netty Herawati (Ensiklopedia Education Review, 2020)
Hypertension is the main cause of stroke which brings high mortality. The cause of hypertension consists of genetic and environmental factors, Along with the changing lifestyle of hypertension cases continues to increase. According to the WHO International Hypertension Society there are currently 600 million sufferers worldwide, and 3 million of them die each year. Based on the results of interviews with hypertension patients who visited the Tanjung Paku Puskesmas among the elderly, said if their high blood pressure always went to the Puskesmas and took hypertension medication, but still rarely did non-pharmacological treatment, so far it was more likely if there were complaints such as headaches, shoulders feels heavy then go straight to the health center. This type of research in this study is a pre-experimental design "One Pre-Test-Post Test Design" in this study the group of subjects was measured blood pressure before deep breathing techniques (pre-test), then carried out deep breating (intervention) and measured again pressure blood after deep breating technique (post test). From the statistical test there was a significant difference between systole blood pressure before and after the deep breathing technique with a p value of 0,000 ˃ 0.05. It is expected that health workers can provide more optimal information, especially for patients with hypertension both mild, mild, moderate and severe to help hypertension sufferers in lowering blood pressure in a non-pharmacological manner.